Experiences and Perceptions of Hospital Social Workers Regarding Discharge Planning and Readmission (International Journal of Scientific Research and Management (IJSRM), 2025)
The Centers for Medicare and Medicaid Services created the Hospital Readmission Reduction Program in 2010 to decrease the problem of hospital readmissions. This program reduces hospital reimbursements from Medicare or Medicaid when patients with specific diagnoses are readmitted within 30 days of discharge. This generic qualitative study explored hospital social workers’ experiences and perceptions of the impact of discharge planning on hospital readmission. Meleis’s transitions theory provided the conceptual framework for this study. Data were collected from semistructured interviews with 10 female medical social workers. Data analysis entailed categorizing and classifying the data into emerging themes to answer the research question. The themes were (a) lack of community resources, (b) hospital administrative challenges, (c) lack of family/social support, and (d) RN versus social worker issues/lack of role definition. Recommendations include standardizing health care social worker roles and providing more time for complex patients to ensure the implementation of all needed services before discharge. Implications for social change include improved discharge planning outcomes, increased support from administration, and consistent social worker role definition and tasks. Positive social change is possible at the policy level because findings showed that providing enough care for patients can reduce hospital readmissions.